Influence of Potassium and Sodium chloride on Germination Behaviour, Biochemical Changes, and Enzyme Activity in Two Varieties of Ocimum tenuiflorum L. Issue 1 (2nd January 2021) - Gupta, Akancha; Singh, Vagmi; Prasad, Priyanka; Kumar, Mukesh; Srivastava, Aishwarya; Singh, Vivek; Luqman, Suaib; Kumar, Birendra
Abstract: Ocimum species are widely distributed throughout the sub-tropical and tropical regions of the world. The present study was conducted to assess the effect of potassium and sodium chloride-induced stress on germination percentage, seedling vigor index along with biochemical parameters like carbohydrate, protein, catalase, total phenolic content, and proline of two Ocimum tenuiflorum varieties viz. CIM-Ayu and CIM-Angana at four different salt concentrations (control, 50 mM, 100 mM, 150 mM). The results revealed that CIM-Angana has superior adaptation and tolerance potential (up to 50 mM) than CIM-Ayu by depicting a higher percentage of germination and seedling vigor index along with elevated levels of biochemical and enzymatic parameters. The variety CIM-Angana was found to be more salt-tolerant than CIM-Ayu. Therefore, it could be suggested to raise the nursery of CIM-Angana under normal conditions of the soil and after that seedlings can be transplanted in presence of salinity up to 50 mM of NaCl or/and KCl salts.